2017
DOI: 10.3389/fcimb.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

The Tudor Staphylococcal Nuclease Protein of Entamoeba histolytica Participates in Transcription Regulation and Stress Response

Abstract: Entamoeba histolytica is the protozoa parasite responsible of human amoebiasis, disease that causes from 40,000 to 100,000 deaths annually worldwide. However, few are known about the expression regulation of molecules involved in its pathogenicity. Transcription of some virulence-related genes is positively controlled by the cis-regulatory element named URE1. Previously we identified the transcription factor that binds to URE1, which displayed a nuclear and cytoplasmic localization. This protein belongs to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Notably, TSN can bind to upstream regulatory element 1 (URE1), which is related to an amoeba virulence protein. It has been suggested that TSN plays a role in virulence regulation as a transcription factor (Calixto-Gálvez et al, 2011;Cázares-Apátiga et al, 2017). In addition, after heat shock treatment (42 °C for 2 h), TSN colocalized with HSP70 (another protein in Entamoeba-shed EVs).…”
Section: Effects Of Extracellular Vesicles On Amebiasismentioning
confidence: 99%
“…Notably, TSN can bind to upstream regulatory element 1 (URE1), which is related to an amoeba virulence protein. It has been suggested that TSN plays a role in virulence regulation as a transcription factor (Calixto-Gálvez et al, 2011;Cázares-Apátiga et al, 2017). In addition, after heat shock treatment (42 °C for 2 h), TSN colocalized with HSP70 (another protein in Entamoeba-shed EVs).…”
Section: Effects Of Extracellular Vesicles On Amebiasismentioning
confidence: 99%
“…1), although the EhPRMTA recombinant protein displayed enzymatic activity on commercial histones (Medina-Gómez et al ., 2021). On the other hand, EhPRMTA interacts with the EhTSN protein, which is a transcription factor of E. histolytica (Cázares-Apátiga et al ., 2017) and its homologues in other protozoan parasites participate in RNA metabolism (Hossain et al ., 2008; Musiyenko et al ., 2012), suggesting that this EhPRMT is involved in transcription regulation and in RNA metabolism; moreover, the EhPRMTA-knockdown increased cell growth and phagocytosis, but decreased cell migration and survival of trophozoites submitted to heat shock (Medina-Gómez et al ., 2021), indicating that this PRMT participates in these events (Table 1), although the identification of its protein targets remains to be determined.…”
Section: Arginine Methylation and Prmts In Protozoan Parasitesmentioning
confidence: 99%
“…Two recent lines of evidence suggest that TSN might be important for assembly and/or function of SGs. First, TSN localizes in SGs in such distant lineages as protozoa, animals and plants (Zhu et al , 2013 ; Yan et al , 2014 ; Gao et al , 2015 ; Gutierrez‐Beltran et al , 2015b ; Cazares‐Apatiga et al , 2017 ). Second, TSN interacts with proteins constituting the core of SGs, such as PAB1, eIF4E and eIF5A in different organisms including mammalian and Bombyx mori cells (Weissbach & Scadden, 2012 ; Zhu et al , 2013 ; Gao et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%